Effect of hybridization on reproductive performance of Oreochromis karongae, Oreochromis shiranus and Oreochromis mossambicus. (26th September 2020) - Nzohabonayo, Elysee; Manyala, Julius; Kang'ombe, Jeremiah; Kassam, Daud
Abstract: The study assessed the effect of hybridization on reproductive performance of Oreochromis karongae, Oreochromis shiranus and Oreochromis mossambicus for a period of 120 days. Number of eggs per batch, number of females spawned, relative fecundity, egg size, hatching period, hatchability and hatchling survival were assessed. The results revealed higher number of eggs per batch and relative fecundity in the crosses where O. shiranus and O. mossambicus were females than female O. karongae . The results also revealed that egg size, hatching period, hatchability and hatchling survival were species specific. Significant differences were noted for number of eggs and larvae produced by the three species ( p < .05). Interspecific and pure crosses for the same female species did not differ significantly for the number of eggs per batch, relative fecundity, egg size, hatching period, hatchability and hatchling survival. However, number of female spawned was found to be higher in the interspecific crosses of female O. karongae than in pure cross of O. karongae . Findings from this study suggest that hybridization can be used to improve reproductive performance of O. karongae as the females spawned increased, and it is a value addition in aquaculture management of indigenous species.